2002
DOI: 10.1186/1297-9686-34-6-729
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among twelve Chinese indigenous goat populations based on microsatellite analysis

Abstract: -Twelve Chinese indigenous goat populations were genotyped for twenty-six microsatellite markers recommended by the EU Sheep and Goat Biodiversity Project. A total of 452 goats were tested. Seventeen of the 26 microsatellite markers used in this analysis had four or more alleles. The mean expected heterozygosity and the mean observed heterozygosity for the population varied from 0.611 to 0.784 and 0.602 to 0.783 respectively. The mean F ST (0.105) demonstrated that about 89.5% of the total genetic variation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
50
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 17 publications
13
50
3
6
Order By: Relevance
“…Contrary to reported microsatellite data from domestic goat breeds, which displayed 5.6-6.8 alleles per locus and mean expected heterozygosities of 0.57-0.79 (Luikart et al, 1999;Saitbekova et al, 1999;Li et al, 2002), the SI subspecies showed considerably low levels of both heterozygosity and allelic diversity ( Table 3), suggesting that the demographic decline of the SI resulted in an overall reduction of genetic diversity at the genome level. Observed (H o ¼ 0.266-0.333) and expected (H e ¼ 0.342-0.485) heterozygosities become higher if monomorphic microsatellites are excluded from the analysis of genetic diversity, but they are still remarkably small.…”
Section: Amills Et Alcontrasting
confidence: 48%
“…Contrary to reported microsatellite data from domestic goat breeds, which displayed 5.6-6.8 alleles per locus and mean expected heterozygosities of 0.57-0.79 (Luikart et al, 1999;Saitbekova et al, 1999;Li et al, 2002), the SI subspecies showed considerably low levels of both heterozygosity and allelic diversity ( Table 3), suggesting that the demographic decline of the SI resulted in an overall reduction of genetic diversity at the genome level. Observed (H o ¼ 0.266-0.333) and expected (H e ¼ 0.342-0.485) heterozygosities become higher if monomorphic microsatellites are excluded from the analysis of genetic diversity, but they are still remarkably small.…”
Section: Amills Et Alcontrasting
confidence: 48%
“…The number of alleles observed in genetic studies is also associated with sample size. Some studies using microsatellite markers sampled more than 50 individuals from each population (Li et al, 2002), more than used in the presented study. However, according to Hale et al (2012), for precise estimates of allele frequencies and genetic diversity, no more than 25 to 30 individuals are needed per population.…”
Section: Discussionmentioning
confidence: 99%
“…We would argue that traditional classification criteria alone cannot explain the substructure of Y-chromosome variation in north Ethiopian cattle populations. It has also been suggested that the topography, which contributes much to the wide variation in climate, soil, natural vegetation and settlement pattern of domestic species, has strongly influenced the distribution of cattle regionally and continentally (Kantanen et al, 2000;Hanotte et al, 2002;Li et al, 2002). The topography of the region is best described as a complex blend of highland (Arado), rugged terrain (Irob), lowland (Abergelle and Begait), steppe and semi-desert (Afra and Raya), and plain (Fogrea).…”
Section: Y-chromosome Microsatellites In North Ethiopian Cattlementioning
confidence: 99%